STRATEGI KREATIF SUTRADARA DALAM CASTING DAN DIRECTING PEMERAN TOKOH AMON PADA FILM PABARUAK - Vianda, Mustika Loly; Girsang, Nitasri Murawaty (Offscreen, 2024)
This study aims to describe the director's creative strategy on casting and directing the character of Amon in the Pabaruak movie. Using the theory creative strategy of Mell Rhodes The Four P'S Creativity (4P) and the theory of Director Don Livingston, casting, Amateur Actor. And also using the descriptive qualitative as the method of the study. The results of this study indicate the creative strategy on casting was carried out immediately and parallelly, which is the first casting was performed by Dafriansyah Putra as a representative of the Triangle System. The casting was carried out by distributed the casting flyers and visited 3 elementary schools in Batusangkar with the recommendation of Mr. Yusuf as a Chair of the Committee. Because of there was no agency or community to provided the children actors, the director decided to used the amateur actors. On the directed process, the director’s strategy creative in directed the amateur children actors with the intense rehearsal process. In some difficult scenes, such as dancing on the peaks, Finally Daanish was able to do silat, because of his intense training process.